Photoactivated disinfection in periodontal treatment: A randomized controlled clinical split‐mouth trial. Issue 11 (31st July 2019) - Husejnagic, Selma; Lettner, Stefan; Laky, Markus; Georgopoulos, Apostolos; Moritz, Andreas; Rausch‐Fan, Xiaohui
Abstract: Background: Photoactivated disinfection (PAD) could support the periodontal treatment outcome. The effect of the light emitting diode (LED) as an innovative light source in PAD is under discussion. The aim of this study was to evaluate the clinical and microbiological effect of adjunctive PAD in the treatment of periodontitis with a red LED as light source. Methods: Twenty patients with periodontitis completed this split‐mouth study. The left and right side of the jaws were randomly assigned to either test or control group. After conservative periodontal treatment in both groups, the test group received two sessions of adjunctive PAD (red LED, 635 nm, photosensitive dye, 0.01% tolonium chloride), whereas the control group received no adjunctive PAD. The parameters of clinical periodontal examination—including probing depth (PD), clinical attachment level (CAL), bleeding on probing (BOP) and microbiological assays (PCR) were evaluated before and after treatment. Results: After 3 months, both treatment groups showed significant improvements regarding BOP, PD, and CAL compared to baseline, with no significant difference between control and treatment group. The recolonization of Porphyromonas gingivalis and Treponema denticola was reduced after adjuvant treatment, but not significantly. Conclusions: The positive effect of adjunctive PAD regarding clinical parameters was reported in recent trials. In this study and with the current settings, both treatment groups showed similar clinical results after initial periodontal treatment, without beneficial effect of adjunctive PAD.